Optimal growth under socially responsible investment: A dynamic theoretical model of the trade-off between financial gains and emotional rewards - Orlando Gomes (International Journal of Corporate Social Responsibility (JCSR), 2020)
Socially responsible investment (SRI) evolved, along the last two decades, from an almost unexplored topic inscience to a recurrent theme of research and debate in Economics and Finance. The growing interest on the theme has two fundamental causes. On one hand, empirical evidence unveils a change of behavior of investors, who typically no longer restrict their decision-making to a strict financial analysis; ethical, social, environmental, and political concerns are also on the forefront of investors' assessments. On the other hand, the economic science is witnessing a paradigm shift characterized by a progressive departure from the orthodox rational deliberation framework and in the direction of the introduction of behavioral elements. In this study, an intertemporal model is proposed to serve as a benchmark for the evaluation of the implications of social and environmental awareness upon investors' decisions and investment performance. The model is a simple optimal control framework that highlights the trade-off between financial returns and the satisfaction emanating from investing in firms or projects guided by ethical values and by good governance principles. Better financial outcomes may come with a social damage that the representative agent in the model will include, with a negative sign, in her utility function. Long-term steady-state results and transitional dynamics are duly evaluated for neoclassical and endogenous growth versions of the model.
Keywords: G41; O41; 650; Socially responsible investment; Ethical investment; Warm-glow effect; Intertemporal optimization; Endogenous growth; Transitional dynamics